Circadian Rhythms in the CNS and Peripheral Clock Disorders: Chronopharmacological Findings on Antitumor Drugs - Shigehiro Ohdo (Elsevier, 2007)
The effectiveness and toxicity of antitumor drugs vary depending on dosing time associated with the 24-h rhythms of biochemical, physiological, and behavioral processes under the control of the circadian clock. Such chronopharmacological phenomena are influenced by not only the pharmacokinetics but also pharmacodynamics of medications. For example, the antitumor effect and/or toxicity of irinotecan hydrochloride, interferon, and antiangiogenic agents vary depending on the dosing time associated with the 24-h rhythm of their target enzyme, receptor, protein, and pharmacokinetics. Many of them are controlled by clock genes. Chronotherapy is especially relevant when the risk and/or intensity of the symptoms of disease vary predicably over time. In a randomized multicenter trial involving patients with previously untreated metastases from colorectal cancer, the chronomodulated infusion of oxaliplatin, fluorouracil (5-FU), and folinic acid is compared with a constant-rate infusion method. Side effects such as stomatitis, peripheral sensory neuropathy are lower and the objective response is higher in the chronotherapy as compared with the fixed-rate infusion. The merit of chronomodulated infusion is supported by the 24-h rhythm of DNA synthesis and the activity of dehydropyrimidine dehydrogenase, which brings about the intracellular catabolism of 5-FU. Although interferon (IFN) also alters the clock function, the disruptive effect of IFN on clock function can be overcome by devising a dosing regimen that minimizes adverse drug effects on clock function. Thus one approach to increasing the efficiency of pharmacotherapy is the administration of drugs at times at which they are most effective and/or best tolerated. Keywords:: chronopharmacology, chronotherapy, chronopharmacokinetics, circadian rhythm, clock gene